A mutual comparison of pregnancy outcomes between different conception modes: a propensity score matching based retrospective cohort study - Sun, Chang-Fa; Sheng, Jian-Zhong; Huang, He-Feng (Frontiers in Endocrinology, 2024)
Background: Assisted reproductive technology (ART) has been reported to have negative effects on maternal and neonatal health. Ovulation induction (OI) was reported to be associated with alteration of epigenetic modification of mice embryos, and extinguishing the influence of ovulation induction and in vitro operations on maternal and neonatal health will bring benefits for reducing sideeffectsside effects. The present study aimed to determine whether ovulation induction alone and ART are associated with adverse pregnancy outcomes and whether ART could induce a higher risk than ovulation induction alone.Methods: This retrospective cohort study was conducted in the International Peace Maternal and Child Health Hospital. A total of 51,172 cases with singleton live birth between Jan 2016 and May 2019 were included in this study. Conception modes documented during registration were classified into natural conception (NC), OI, and ART. Pregnancy outcomes of the three groups with balanced baseline characteristics by propensity score matching were compared. The relative risks of maternal and neonatal outcomes were calculated by logistic regression analysis.